Analisis Model Pendidikan Induksi Pada Anak Yang Mengalami Gerakan Dan Gangguan Motorik Di Sekolah Sd/Mi - Awaluddin Hidayat; Indah Mutia; Lili Marzila; Wismanto Wismanto; Aliza Aliza; Hanna Sajiddah (Jurnal Insan Pendidikan dan Sosial Humaniora, 2024)
This article discusses children who experience movement and motor barriers / disabilities, disabilities include children with special needs because they have physical disorders that interfere with movement due to congenital bone structure abnormalities, illness, or due to accidents, such as polio and paralysis, The way to communicate with children with disabilities is by: (1) Everyone must change his perspective on children with disabilities and realize that everyone has disadvantages and advantages; (2) Everyone shall pay attention to the readiness of the school, including its administration, principal, and students; and (3) provide special facilities for persons with disabilities. (4) Embrace them so that they can blend in with the general public and not feel inferior. This research uses a qualitative approach where the data collected for this research is collected through reviews of journals, books, and other sources of information relevant to the research topic Data analysis is carried out through a descriptive approach, which involves data reduction techniques, data analysis, and drawing conclusions. So according to the results of the study there are several causes of disorder 1. Before birth 2. At birth 3. After birth.